2021
DOI: 10.3390/cancers13133279
|View full text |Cite
|
Sign up to set email alerts
|

LRG1 Promotes Metastatic Dissemination of Melanoma through Regulating EGFR/STAT3 Signalling

Abstract: Although less common, melanoma is the deadliest form of skin cancer largely due to its highly metastatic nature. Currently, there are limited treatment options for metastatic melanoma and many of them could cause serious side effects. A better understanding of the molecular mechanisms underlying the complex disease pathophysiology of metastatic melanoma may lead to the identification of novel therapeutic targets and facilitate the development of targeted therapeutics. In this study, we investigated the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Activation of the TGFβ-related transcription factors HIF-1α [ 197 ] and RUNX1 [ 50 ] has also been associated with LRG1 pro-oncogenic functions, although the specific upstream pathways subject to LRG1 modification in this context remain to be formally clarified. Additional transduction factors involved in LRG1 signalling include (i) EGFR which promotes pancreatic cancer cell malignancy through p38/MAPK [ 49 ], dissemination of melanoma cells [ 90 ] and cornea repair through STAT3 [ 64 ]; (ii) the IL-6/STAT3 axis which modulates neutrophil chemotaxis [ 57 ]; (iii) Wnt/βcatenin which, in the heart, inhibit fibroblast proliferation and migration [ 37 ]. Further investigations are needed to address whether LRG1 modulates the activity of other receptor-mediated signalling pathways including BMPs, and whether other receptors may also be directly or indirectly affected by LRG1.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the TGFβ-related transcription factors HIF-1α [ 197 ] and RUNX1 [ 50 ] has also been associated with LRG1 pro-oncogenic functions, although the specific upstream pathways subject to LRG1 modification in this context remain to be formally clarified. Additional transduction factors involved in LRG1 signalling include (i) EGFR which promotes pancreatic cancer cell malignancy through p38/MAPK [ 49 ], dissemination of melanoma cells [ 90 ] and cornea repair through STAT3 [ 64 ]; (ii) the IL-6/STAT3 axis which modulates neutrophil chemotaxis [ 57 ]; (iii) Wnt/βcatenin which, in the heart, inhibit fibroblast proliferation and migration [ 37 ]. Further investigations are needed to address whether LRG1 modulates the activity of other receptor-mediated signalling pathways including BMPs, and whether other receptors may also be directly or indirectly affected by LRG1.…”
Section: Reviewmentioning
confidence: 99%
“…6 ). Indeed, epidermal growth factor receptor (EGFR) has been shown to mediate LRG1 activity in pancreatic cancer cells [ 49 ], metastatic melanoma cells [ 90 ], and corneal epithelium during wound repair [ 64 ], whereas the IL-6/STAT3 axis appears to modulate LRG1-driven neutrophil chemotaxis [ 57 ]. Therefore, one may speculate that LRG1 interferes with the activity of different receptors in a context-dependent manner and that functional outcomes will be most likely determined by the balance between various interacting pathways.…”
Section: Reviewmentioning
confidence: 99%
“…7a ). Recently, STAT3 signaling was also reported to be involved in LRG1-promoted metastatic dissemination of melanoma [ 31 ]. Whereas, p-STAT3 blockade by pacritinib showed little effect on LRG1-induced EMT in CRCs (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Melanoma is a classic model to analyze tumor cell migration in clinics and research [ 8 , 9 ] and this collection of Cell Motility and Cancer includes three contributions [ 10 , 11 , 12 ]. An Australian clinical study of 306 metastatic melanomas has found that BRAF + NRAS mutations were associated to the central nervous system and liver metastases, while BRAF mutation was to lymph node metastases and NRAS mutation with lung metastases [ 8 ], so tumor mutation status may advise to direct specifically to these sites the clinical surveillance of these patients.…”
mentioning
confidence: 99%
“…Interestingly, the same group has previously shown that PMCA4b inhibits cell migration and metastatic capacities in BRAF mutant melanoma cells [ 15 ]. Kwan et al [ 12 ] analyze the role of LRG1, a leucine-rich alpha 2 glycoprotein, in melanoma and conclude that this protein is required for metastatic dissemination but not for cell growth.…”
mentioning
confidence: 99%